"São aqueles que não olham que viram pedra" : Medusa e as (re)interpretações do feminino - Diedrich, Bruna (2022)
This master’s thesis investigates the interpretations regarding the origin, death and qualities attributed to the creation and construction of Medusa. Relying on Feminist Epistemologies (especially Standpoint Theory) and on Theories of Subjects as theoretical-methodological instruments, we intend to answer the following research problem: starting from the construction (appearances, origin, death and characteristics) of Medusa, it is possible to raise hypotheses about women as a category of analysis? We aimed to answer through the most diverse representation possible of women, making their representation as a singularity or unique concept implaticable. Intersectionality emerges as a guide, guiding the results, fluidly across themes, investigating how gender stereotypes intersect with other hierarchies of power (especially race and class). The main objective is to analyze the concept of feminine, centered on the rupture and commitment to the representation of multiplicity and diversity, questioning the very unified concept of the woman category. The specific objectives focus on contrasting versions of Greco-Roman poets (Homer, Hesiod, Euripides, Pseudo-Apollodorus and Ovid) about Medusa, exam the female role in mythological narratives, as well as opposing it to the male, reflecting on the role social of myths. The contributions of Feminist Epistemologies are investigated, with emphasis on the Standpoint Theory line, as well as the Subject Theories, in the analysis of the myths that contemplate the figure of Medusa, considering the importance of diversity and social experiences in the processes of acquisition, attribution and knowledge production. Feminist Epistemologies emerge as instrumentalization aimed at breaking with the preconceived notion of universality and objectivity. From the situated knowledge and the identification of the epistemic agent in its subjectivities, it reflects on the social character of the processes. With the inseparable relationship between Epistemology and politics defended by Linda Alcoff, non-epistemic reasons that affect the processes of knowledge legitimation are approached. In addition, there is a concern to provide an overview of the emergence of Standpoint Theory as a theoretical framework, since there is a shortage of translations by the authors. After the discussion of partiality of knowledge, through the Feminist Epistemologies, it is also observed that, even among theorists, there is no consensus or proposal of unity that intends to speak for all women. There is a concern with the representation of more subjects and, for that, the Theories of Subjects were used. Based on concepts such as self-definition and self-assessment (presented by Patricia Hill Collins), a broad and diverse representation of voices and visions was sought. It prioritized marginalized individuals, who are in conflict with the concept of femininity just for existing, echoing their attempts to become a subject through writing (as pointed out by Grada Kilomba). This analysis becomes possible through the following characteristics of Medusa: presentation of the narratives that contemplate the character; death and corporeality; humanization; beauty and femininity; perceptions (the act of seeing, being seen, hearing and being heard); duality and ambiguity; monstrosity and aggressiveness; passivity, silence and supporting role; guilt and punishment. As an adjacent instrument, for a better understanding of the sociocultural perspective, mythology emerges. The main authors of this session are Mircea Eliade, Joseph Campbell, Jean-Pierre Vernant, Pierre Grimal and Pierre Brunel.